Challenges of nuclear waste governance. An international comparison. Vol. 2. - (:unkn) unknown (Springer VS, 2018)
This is volume two of a comparative analysis of nuclear waste governance and public participation in decision-making regarding the storage and siting of high-level radioactive waste and spent fuel in different countries. The contributors examine both the historical and current approaches countries have taken to address the wicked challenge of nuclear waste governance. The analyses discuss the regulations, technology choices, safety criteria, costs and financing issues, compensation schemes, institutional structures, and approaches to public participation found in each country.
Keywords: Umweltschutz; Energiepolitik; Entsorgung; Atomabfall; Endlagerung; Governance; Partizipation; Entscheidungsfindung; Internationaler Vergleich